Pertolongan Pertama pada Kecelakaan dalam Kegiatan Jumpa Bakti Gembira Kota Medan - Putri Rizky; Alda Putriana; Zahra Azzura Jaffa (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
First Aid for Accidents is a temporary relief and treatment effort so that the condition of the accident victim can be better before receiving more complete assistance from a doctor or paramedic. Generally, accidents happen suddenly, without being expected, either because of our fault, other people or circumstances, and can happen anywhere. All victims who experience emergencies really need fast and effective action to maintain life and minimize the occurrence of disability. Based on the problem formulation that has been explained, the researchers carried out research activities at the PMI's Jumpa Bakti Selamat (Jumbara) event in Kampung Outbound, Pancur Batu subdistrict. North Sumatra. The research method used is a qualitative method. There are four types of data collectiontechniques, namely observation, interviews, documentation, and combination/triangulation.Based on the research results obtained, researchers conducted research from different schools. The results of the evaluation through interviews conducted by researchers showed that the majority of PMR members (80%) understand and understand first aid for accidents in general as well as soft tissue injuries,fractures, types of wounds, muscle injuries and are able to practice stopping bleeding and splinting and handling snakebite. Participants were happy with this training, this was proven by the number of participants who were active in discussions and asked questions and were enthusiastic when asked and were able to practice how to stop bleeding and apply splints and treat snake bites.